SEBUAH GAGASAN PENGEMBANGAN APLIKAISI TEKNOLOGI INFORMASI UNTUK MENDUKUNG PENDIDI KAN MAHASISWA STRATA.I BIDANG EKONOMI PERUSAHAAN - Michael Iskandar (Center for Economic Studies Universitas Katolik Parahyangan, 2005)
Universities nowadays are under increasing pressure to produce graduates who are not only knowledgeable but who also have valuable work experience as well as excellent interpersonal skills. The last two are often lacking in the university graduates of today, which will be to their detriment when-they enter the workforce looking for good, well-paid jobs with long- range prospects. This paper introduces an idea to include a continuous, lT-enhanced, “work experience